Transglutaminases and Transglutaminase‐Catalyzed Cross‐Links Colocalize with the Pathological Lesions in Alzheimer's Disease Brain - Wilhelmus, Micha M.M. (Brain Pathol, 2008)
Alzheimer's disease (AD) is characterized by pathological lesions, in particular senile plaques (SPs), cerebral amyloid angiopathy (CAA) and neurofibrillary tangles (NFTs), predominantly consisting of self‐aggregated proteins amyloid beta (Aβ) and tau, respectively. Transglutaminases (TGs) are inducible enzymes, capable of modifying conformational and/or structural properties of proteins by inducing molecular covalent cross‐links. Both Aβ and tau are substrates for TG cross‐linking activity, which links TGs to the aggregation process of both proteins in AD brain. The aim of this study was to investigate the association of transglutaminase 1 (TG1), transglutaminase 2 (TG2) and TG‐catalyzed cross‐links with the pathological lesions of AD using immunohistochemistry. We observed immunoreactivity for TG1, TG2 and TG‐catalyzed cross‐links in NFTs. In addition, both TG2 and TG‐catalyzed cross‐links colocalized with Aβ in SPs. Furthermore, both TG2 and TG‐catalyzed cross‐links were associated with CAA. We conclude that these TGs demonstrate cross‐linking activity in AD lesions, which suggests that both TG1 and TG2 are likely involved in the protein aggregation processes underlying the formation of SPs, CAA and/or NFTs in AD brain.